We burn daylight eaudiobook A novel. - Johnston, Bret Anthony (Books on Tape, 2024)
NATIONAL BESTSELLER • An epic novel of star-crossed lovers set in a doomsday cult on the Texas prairie that asks: What would you sacrifice for the person you love? “Symphonic and suspenseful . . . In an epic act of empathy, Bret Anthony Johnston inhabits every point of view, from doomed devotees to perplexed law enforcement.”—Geraldine Brooks, Pulitzer Prize–winning author of March A New York Times Book Review Editors’ Choice Waco, Texas, 1993. People from all walks of life have arrived to follow the Lamb’s gospel—signing over savings and pensions, selling their homes and shedding marriages. They’ve come here to worship at the feet of a former landscaper turned prophet who is preparing for the End Times with a staggering cache of weapons. Jaye’s mother is one of his newest and most devout followers, though Jaye herself has suspicions about the Lamb’s methods—and his motives. Roy is the youngest son of the local sheriff, a fourteen-year-old boy with a heart of gold and a nose for trouble who falls for Jaye without knowing of her mother’s attachment to the man who is currently making his father’s life hell. The two teenagers are drawn to each other immediately and completely, but their love may have dire consequences for their families. The Lamb has plans for them all—especially Jaye—and as his preaching and scheming move them closer and closer to unthinkable violence, Roy risks everything to save Jaye. Based on the true events that unfolded thirty years ago during the siege of the Branch Davidian compound, Bret Anthony Johnston’s We Burn Daylight is an unforgettable love story, a heart-pounding literary page turner, and a profound exploration of faith, family, and what it means to truly be saved.